Breast conservation surgery by round block mammoplasty. Issue 2 (February 2020) - Burrah, Rajaram; James, Karen; Lund, Jonathan; Vinayagam, Raman
Abstract: Background: Round block mammoplasty (RBM) is a type of Oncoplastic procedure to facilitate breast conservation surgery for breast cancer. Methods: Retrospective study of 270 patients who underwent this surgery. The surgical and oncological outcomes of RBM were studied. Results: The median age was 61 years and median follow-up 39 months. Most cancers (59%) were screen-detected. The location of the cancer was commonly in the upper outer quadrant followed by upper inner quadrant (20%). The average tumor size was 18 mm and in 48% of patients the whole tumor size increased to 23.5 mm due to associated DCIS. The median specimen weight was 41 gm. Forty patients (14.8%) had positive margins. Postoperative complications were seen in 18 patients (6.6%). There were 4 local and 1 axillary recurrences, and 8 distant metastasis. Contralateral symmetrising surgery was required in 13 patients (4.8%). Conclusion: RBM is a robust and easily adaptable technique which provides good exposure for a safe oncological excision. The surgical and oncological outcomes are good and contralateral symmetrising surgery is rarely required.